Red Blood Cell Membrane Fatty Acids in U. S. Blood Donors (P06-123-19). (13th June 2019) - Powers, Carissa; Scully, David; Schleicher, Rosemary
Abstract: Objectives: The purpose of this study was to use a newly validated method for measuring 21 cis -fatty acids in red blood cell (RBC) membranes to investigate race-ethnic and gender differences in saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA). In addition, two long-chain PUFA, namely, eicosapentaenoic (EPA) and docosahexaenoic acid (DHA), were summed to provide an Omega-3 Index for each participant. This index is considered a cardiovascular risk factor. Methods: Units (n = 120) of whole blood in EDTA were purchased from BioIVT (Westbury, NY). The demographic make-up of the set was 60:60 men: women. Of the 120 blood donors, 37% were black, 29% were white, and 34% were Hispanic. Average ages were 44 y (black), 48 y (white), and 43 y (Hispanic). Upon arrival, units were washed, treated with 1% BHT, and packed RBC were frozen until time of analysis. Hydrolysis of esters, derivitization with pentafluorobenzyl bromide, gas chromatography, and mass spectrometric detection were carried out to measure the 21 most abundant cis -fatty acid concentrations in RBC, which were converted to weight percentages of total. For the Omega-3 Index, the percentage of totals calculated for EPA and DHA were summed. Results: There were few small (≤1%) race-ethnic differences and no gender differences in the proportions of fatty acids as SFA, MUFA, or PUFA; overall these averaged (SD) 44% (1%), 16% (1%), and 40% (1%), respectively. The Omega-3 Index averaged (SD) 3.5% (1%). One blood donor reached the suggested goal of ≥ 8%, which is associated with low risk for cardiac events. Conclusions: This small study was undertaken in advance of the U.S. nationally representative survey, NHANES 2019–2020, in which RBC membrane fatty acids will be measured in the same laboratory. It will be interesting to learn whether NHANES will confirm the mostly null demographic findings in RBC fatty acid percentages and the low average Omega-3 Index. Funding Sources: None.